New species and records of Anacroneuria (Plecoptera: Perlidae) from the northeastern semi-arid region of Brazil - Duarte, Tácio; Lecci, Lucas Silveira (Zootaxa, 2016)
The genus Anacroneuria is widely distributed in the Neotropical Region. There are about 80 species listed from Brazil, five of which are recorded from the northeastern semi-arid region of Brazil, an area characterized by irregular and low precipitation. Examination of adult Anacroneuria material from this including areas of Caatinga desert vegetation and Atlantic forest revealed two new species records, A. debilis (Pictet) and A. terere Righi-Cavallaro & Lecci. Additionally, two new species, A. calori n. sp. and A. singela n. sp., are described from this material. These new records and new species reflect a major effort to document the biodiversity of the aquatic insects of the northeastern semi-arid region of Brazil by the Research Program in Semi-arid Biodiversity.